When Comes Lack of „Swiss Precision” – Few Words in Legal and Economic Aspect About Loans in Swiss Franc Taken by Polish Debtors - Liwoch, Piotr (Journal of Finance and Financial Law, 2017)
Article shows the main problems of loans incurred in Suiss francs by polish debtors in period of time 2007–2015. Author sets out with the aim of analysing polish financial market and tries to answer a questions about banks’ responsibility for increased debtors’ commitments, presents judgments of courts of law and evaluates legislative actions, which are expected to help polish debtors. Author points at necessity of foreign currency loans risk reduction.